A fibrinogen-based patch and its preparation method and application
The fibrinogen patch prepared by modifying the lysine residue of fibrinogen to contain hydrophobic groups and combining with stabilizers, solves the problem of insufficient mechanical strength and adhesion performance of the existing fibrinogen hemostatic agent, and achieves better hemostatic effect and biocompatibility.
Patent Information
- Application Number
- CN202310515045.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-05-09
AI Technical Summary
The existing fibrin glue hemostatic agents have shortcomings in terms of mechanical strength and adhesion properties, resulting in unsatisfactory hemostatic effect.
A fibrinogen patch with excellent mechanical strength and adhesion properties was prepared by modifying part of the lysine residues of fibrinogen to contain hydrophobic groups and combining with a stabilizer.
The patch can quickly and efficiently achieve blocking without relying on added thrombin, significantly improve hemostatic performance, and have good biological activity and biocompatibility.
Smart Images

Figure CN116531551B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fibrinogen-based patch and a preparation method and application thereof, and belongs to the field of medical tissue engineering. Background Art
[0002] Uncontrolled bleeding after trauma or during surgery is the leading cause of death worldwide, resulting in more than 2 million deaths each year. It is necessary and critical to minimize blood loss during surgical procedures, seal tissue and organ structures, reduce post-surgical complications and surgical time in the operating room. Wound dressings and tissue adhesives are devices used to prevent leakage of blood and other body fluids.
[0003] Commonly used surgical hemostatic agents include fibrin glue, gelatin and oxidized cellulose. Among them, fibrin glue is one of the most widely used hemostatic agents due to its good procoagulant properties and biocompatibility. Its mechanism of action is to simulate the last step of the enzyme cascade reaction in the human body's autologous coagulation reaction process, using thrombin to convert fibrinogen into fibrin monomers, which are cross-linked into a fibrin glue network to seal the wound and play a hemostatic role. The mechanical strength of fibrin glue has poor adhesion properties and cannot achieve efficient adhesion and closure of wounded wet tissues. Although fibrin glue has high procoagulant properties, the hemostatic effect is not very ideal. So, how to enhance the mechanical strength of fibrin gel is a key challenge to solve the weak hemostatic performance.
[0004] The physical and mechanical strength of fibrin glue depends on the structure of fibrin monomers, the cross-linked network structure of fibrin glue and the degree of cross-linking. Fibrinogen is an oligosaccharide protein with a molecular weight of 340 kDa, consisting of two symmetrical halves, each of which contains three polypeptide chains: Aα, Bβ and γ. Fibrinogen is cleaved by thrombin to release the peptide chains FpA and FpB. The exposed amino acid residues of the formed fibrin monomer complement the other fibrin monomer to form a "knob-hole interaction", which eventually extends, alternates and overlaps to form a cross-linked network structure of fibrin glue. At present, the means to improve the mechanical strength of fibrin glue mainly include: regulating the concentration of fibrinogen and thrombin, and introducing filling proteins. First, according to literature reports, the concentration of thrombin affects the thickness of the fibrils formed by fibrin, which is related to the mechanical strength of fibrin glue. Initially, researchers improved the mechanical properties by adjusting the concentration of fibrinogen and thrombin in fibrin glue. Therefore, the concentrations of fibrinogen and thrombin in commercial fibrin glues (Tisseel, Evicel, Hemaseel, etc.) are different, but the mechanical properties of adhesion have not been significantly improved. Second, scientists have improved the overall mechanical properties of hydrogels by introducing proteins into the gel network. Researchers have improved the mechanical strength by adding collagen and gelatin (such as CoStasis, etc.) as filling materials for the fibrin glue network structure, but the improvement is still limited. In addition, there are also methods to fix fibrinogen and thrombin on a carrier to improve mechanical properties. TachoSil FibrinSealant Patch is a sealant that loads human fibrinogen and thrombin on horse collagen sponge. When TachoSil is applied to bleeding or other body fluid areas, moisture will cause thrombin to shear fibrinogen, quickly forming a clot of fibrin glue, which adheres to the tissue surface to achieve hemostasis and wound sealing. However, it is a relatively time-consuming process for the sponge to absorb water to dissolve fibrinogen, which is not conducive to the rapid sealing of blood-containing wounds; similarly, its performance still mainly depends on the mechanical properties of the fibrin glue itself, and the overall hemostasis and sealing performance are limited. According to literature reports, in a pig liver injury bleeding model (10mm diameter, 10mm deep notch), after pressing the wound with a TachoSil patch for 3 minutes, the wound was not successfully sealed and blood continued to flow out (Nature Biomedical Engineering 5, 1131–1142 (2021)). Therefore, although fibrinogen / glue has excellent procoagulant properties and biocompatibility, its mechanical strength (intrinsic strength and adhesion properties) has not been significantly improved under the improvement of existing technologies.
[0005] In order to achieve a breakthrough in the hemostatic performance of fibrinogen / glue, the key lies in: how to regulate the composition and structure of fibrinogen / glue itself to improve its mechanical strength and adhesion properties? Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a fibrinogen-based patch and a preparation method and application thereof. The present invention unexpectedly obtains a new tissue patch by a simple method. Through structural improvement, the patch has excellent mechanical strength and adhesion performance, can be better applied to hemostasis or tissue adhesion, and can achieve closure quickly and efficiently.
[0007] The present invention adopts the following technical method:
[0008] A fibrinogen-based patch comprises fibrinogen and a stabilizer, wherein some lysine residues of the fibrinogen contain hydrophobic groups; and the stabilizer is used for maintaining the activity of the fibrinogen.
[0009] In the above technical solution, the stabilizer used to maintain the activity of fibrinogen not only refers to maintaining the spatial structure and biological activity of fibrinogen, but also includes maintaining the stability of fibrinogen in the patch state and during the patch manufacturing process. The stabilizer can generally be one or more of sodium chloride, calcium chloride, potassium chloride, magnesium chloride, sodium citrate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, arginine hydrochloride, and glycine.
[0010] The hydrophobic group is a hydrocarbon group containing one or more groups of a carbonyl group, a carbon-carbon double bond, an ester group, an amide bond, and a phenyl group.
[0011] Preferably, the hydrophobic group is -CO-(CH2) n CH3, n = 1-19; more preferably, the hydrophobic group is -CO-(CH2) n CH3, n = 2-10; most preferably, the hydrophobic group is -CO-(CH2) n CH3, n=3-6.
[0012] Preferably, the hydrophobic group forms an amide bond (—NH—CO—) with the primary amine of the lysine residue of fibrinogen.
[0013] The lysine residues containing hydrophobic groups on the fibrinogen account for 2%-70% of the total number of lysine residues, calculated by number; the total number of lysine residues is the sum of the lysine residues containing hydrophobic groups and the unmodified lysine residues.
[0014] Preferably, the lysine residues containing hydrophobic groups on the fibrinogen account for 5%-40% of the total lysine residues; more preferably, the lysine residues containing hydrophobic groups on the fibrinogen account for 10%-30% of the total lysine residues.
[0015] The ratio of the lysine residues containing hydrophobic groups on the fibrinogen to the total number of lysine residues needs to be within a specific range to ensure that the micro-level fibrinogen molecules containing hydrophobic groups are entangled with each other, so that the mechanical properties of the fibrinogen patch are reflected at the macro level. If the ratio of the lysine residues containing hydrophobic groups on the fibrinogen to the total number of lysine residues is too low, such as less than 2%, the mechanical properties of the fibrinogen patch relative to the unmodified fibrinogen patch at the macro level do not change significantly. If the ratio of the lysine residues containing hydrophobic groups on the fibrinogen to the total number of lysine residues is higher than 70%, due to the replacement of a large amount of basic amino acids (lysine) on the protein surface, fibrinogen protein denaturation and spatial structure instability can be caused, which ultimately leads to the deterioration of the mechanical properties of the patch, even less than the original unmodified fibrinogen. Therefore, the degree of modification of lysine residues in a specific ratio is conducive to realizing the high mechanical properties of modified fibrinogen.
[0016] The patch contains no less than 2 mg of fibrinogen containing hydrophobic groups per square centimeter. Preferably, the patch contains 4 to 100 mg of fibrinogen containing hydrophobic groups per square centimeter; preferably, the patch contains 10 to 50 mg of fibrinogen containing hydrophobic groups per square centimeter; more preferably, the patch contains 20 to 30 mg of fibrinogen containing hydrophobic groups per square centimeter.
[0017] The patch must have at least a certain amount of fibrinogen containing hydrophobic groups per square centimeter to ensure that the patch has continuous and uniform fibrinogen to achieve mechanical properties of a certain strength.
[0018] The fibrinogen may be derived from any one or more of human, bovine, porcine and recombinant sources.
[0019] The fibrinogen-based patch may contain active pharmaceutical ingredients, which are substances with medical or physiological activity and can be used to treat or alleviate disease symptoms. The active pharmaceutical ingredients include drugs for targeted or controlled release. Preferably, the active pharmaceutical ingredients include plasmin inhibitors.
[0020] Preferably, the surgical patch further comprises one or more of collagen, albumin and hyaluronic acid. The collagen is derived from any one or more of human, bovine, porcine, horse and recombinant.
[0021] The present invention also provides a preparation method based on a fibrinogen patch, the specific steps comprising the following:
[0022] ① subjecting a mixed solution of fibrinogen and a stabilizer to ultrasonic treatment, and obtaining a fibrinogen solution having a mass fraction of 5 to 200 mg / mL;
[0023] ② adding a hydrophobic modification reagent dropwise to the fibrinogen solution under stirring, reacting at 37° C. for 0.5 to 5 hours to obtain a fibrinogen solution containing a hydrophobic group;
[0024] ③ The obtained fibrinogen solution containing hydrophobic groups is dialyzed at 4-37°C for 5-72 hours;
[0025] ④ The obtained fibrinogen solution containing hydrophobic groups is concentrated to 50-200 mg / mL at a concentration temperature of 4-37°C; and freeze-dried at a freeze-drying temperature of -85--35°C to obtain a fibrinogen-based patch.
[0026] In the above technical solution, the hydrophobic modification reagent contains a hydrophobic group, and the hydrophobic group is used to modify the fibrinogen lysine residue; the hydrophobic modification reagent also contains a succinimide group, and the succinimide group is used to react with the primary amine of the lysine residue to form a stable amide bond.
[0027] The composition of the hydrophobic modification reagent includes two types of groups, one part of which is used to modify the lysine residues of fibrinogen and is the hydrophobic group of the present invention. The other part of the groups is used to react with the primary amine on the lysine residues of fibrinogen. Finally take off For example, the succinimide group of the present invention reacts with the primary amine on the lysine residue to form a stable amide bond and release N-hydroxysuccinimide (NHS).
[0028] Preferably, the succinimide group contains a sulfonate group (-SO3 - ). The sulfonate group can increase the water solubility of the hydrophobic modification reagent, and more importantly, increase the efficiency of the reaction between the hydrophobic modification reagent and fibrinogen.
[0029] When the hydrophobic modification reagent contains a succinimide group and a hydrophobic group, the reactive group (succinimide group) on the hydrophobic modification reagent can reduce or prevent the hydrophobic modification reagent from inducing protein denaturation of fibrinogen. The hydrophobic modification reagent of the present invention cannot be an acid anhydride with a hydrophobic group. An acid anhydride with a hydrophobic group can easily denature fibrinogen, and the denatured fibrinogen is easily precipitated from the solution, making it impossible to modify the hydrophobic group on the fibrinogen, and even more impossible to form the fibrinogen-based patch of the present invention.
[0030] The hydrophobic group is a hydrocarbon group containing one or more groups of a carbonyl group, a carbon-carbon double bond, an ester group, an amide bond, and a phenyl group.
[0031] Preferably, the hydrophobic group is -CO-(CH2) n CH3, n = 1-19; more preferably, the hydrophobic group is -CO-(CH2) n CH3, n = 2-10; most preferably, the hydrophobic group is -CO-(CH2) n CH3, n=3-6.
[0032] Preferably, the hydrophobic group forms an amide bond (—NH—CO—) with the primary amine of the lysine residue of fibrinogen.
[0033] The invention also provides an application of a fibrinogen-based patch, and the patch can be used for tissue adhesion.
[0034] The patch is used for hemostasis; the hemostasis can be used for hemostasis in cardiovascular, liver, pancreatic and thyroid surgeries; when the patch contacts tissue and / or blood, a coagulation reaction may occur and a clot may be subsequently formed, and based on the strong interaction between fibrinogen molecules, the patch has strong adhesion to nearby tissues. The synergistic effect of these two aspects can effectively prevent, reduce or stop bleeding.
[0035] The patch is used to join structures and / or seal physiological leaks; it is used for leaks of cerebrospinal fluid, lymph, bile, gastrointestinal contents, and for air leaks in the lungs.
[0036] The patch is used to repair damaged tissue, which refers to the destruction of the normal continuity of the tissue structure, such as incisions caused by surgical, biological or chemical means; it also includes contused tissue, as well as cuts, punctures, lacerations, open injuries, penetrating injuries, and puncture injuries caused by tearing, pressure and biting.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] 1. The present invention unexpectedly prepared for the first time a new fibrinogen patch, which includes fibrinogen containing hydrophobic groups. The fibrinogen containing hydrophobic groups has strong intermolecular interactions relative to wild-type (unmodified) fibrinogen. The hydrophobic groups promote the entanglement between fibrinogen protein molecules, forming a patch with super strong mechanical properties and adhesion properties.
[0039] 2. The fibrinogen patch provided by the present invention is independent of the effect of added thrombin and forms a fibrinogen patch by itself. The application of fibrinogen / glue in tissue sealing and hemostasis in the prior art is based on the reaction of fibrinogen and thrombin, and it is not found that fibrinogen alone can play a related role in tissue sealing. Independent of the added thrombin, the cost of materials can be reduced and the problem of enzyme storage difficulties can be eliminated. The existing technologies all rely on dissolving fibrinogen and thrombin to form a solution, or absorbing water to dissolve. Generally, the dissolution process is time-consuming and complicated and needs to be prepared in advance. The patch described in the present invention can be taken as needed during actual application.
[0040] 3. The hydrophobic group-based fibrinogen patch provided by the present invention has good biological activity, can promote cell proliferation and differentiation, and is beneficial to wound healing and recovery of defective tissues; the degradation rate of the patch can be adjusted by changing the composition of the hydrophobic group, thereby meeting the regeneration rate of autologous tissues and organs.
[0041] 4. The preparation method used in the present invention is easy to operate and has a simple process; the obtained patch is easy to use and can be cut according to the size of the wound. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Scanning electron micrograph of the fibrinogen patch of Example 1;
[0043] Figure 2 Molecular dynamics simulation of the interaction between unmodified fibrinogen molecules and the fibrinogen molecules containing hydrophobic groups of the present invention shows that the fibrinogen molecules containing hydrophobic groups have strong interactions, inducing molecular entanglement.
[0044] Figure 3 The time it takes for unmodified fibrinogen and the fibrinogen containing hydrophobic groups of Example 1 of the present invention to be recognized by thrombin to form a fibrin gel;
[0045] Figure 4 The pH and in vitro cytotoxicity corresponding to the Surgicel Fibrillar products of Example 1, Comparative Example 1 and Comparative Example 4;
[0046] Figure 5Shear strength of three surgical adhesive products (Fibrin Glue, Surgicel Fibrillar, Gelatin Sponge) of Example 1, Comparative Example 1 and Comparative Example 4;
[0047] Figure 6 The bonding energy of the three surgical adhesive products (Fibrin Glue, Surgicel Fibrillar, Gelatin Sponge) of Example 1, Comparative Example 1 and Comparative Example 4;
[0048] Figure 7 The hemostasis time and blood loss of the surgical adhesive products (Surgicel Fibrillar, Gelatin Sponge) of Example 1 and Comparative Example 4 in the liver of New Zealand white rabbits;
[0049] Figure 8 Hemostasis time and blood loss of the liver of New Zealand white rabbits using the four emergency hemostasis products (Combat Gauze, HemCon, Celox, ChitoSAM) of Example 1 and Comparative Example 4; Specific embodiments
[0050] The technical problems, technical solutions and beneficial effects to be solved by the present invention are described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can also be made without departing from the inventive concept. These all belong to the protection scope of the present invention.
[0051] The present invention provides a fibrinogen patch with excellent mechanical properties and adhesion properties, the patch comprises fibrinogen and a stabilizer, and some lysine residues of the fibrinogen contain hydrophobic groups. Lysine residues on the surface of fibrinogen are modified with hydrophobic groups, and in a solution state, due to the participation of water molecules (electrostatic action, hydrogen bonds, etc.), the van der Waals interactions of most hydrophobic groups are destroyed. In the process of removing water to form a patch, the van der Waals interaction between the hydrophobic chains is enhanced due to the close interaction, resulting in the fibrinogen patch having strong mechanical properties and adhesion properties. The stabilizer is one or more of sodium chloride, calcium chloride, sodium citrate, sodium dihydrogen phosphate, sodium hydrogen phosphate, arginine hydrochloride, and glycine.
[0052] The stabilizer is used to maintain the spatial structure and biological activity of fibrinogen. The stabilizer is used to maintain the stability of fibrinogen in the patch state and in the process of preparing the patch. The stabilizer is introduced when preparing the fibrinogen solution in the preparation of the patch.
[0053] Shear strength test: refer to the American Society for Testing and Materials standard (ASTM F2255-05). Add a fibrinogen patch to the surface of fresh pig skin, the area of the patch is 10×20mm, and place another pig skin on the surface of the patch to keep the two pig skins overlapping at the patch site. Use a universal material testing machine to test the shear strength of the sample at a strain rate of 5mm / min.
[0054] Adhesion energy test: refer to the American Society for Testing and Materials standard (ASTM F2256-05). Add a fibrinogen patch to the surface of fresh pig skin, the area of the patch is 15×35mm, and place another pig skin on the surface of the patch. Use a universal material testing machine to test the adhesion performance of the sample at a strain rate of 5mm / min.
[0055] New Zealand rabbit liver hemostasis experiment: The liver lobe of New Zealand rabbits (2.5-3 kg) was used, and a 10 mm long and 5 mm deep incision was made on the surface of the liver. The bleeding was allowed to bleed freely for 10 seconds and the amount of bleeding was recorded. The patch was added to the surface of the liver incision and pressed for 15 seconds. The wound closure state, hemostasis time and blood loss of traumatic bleeding were evaluated.
[0056] Example 1
[0057] ① Take a 100 mg / mL fibrinogen solution (PBS buffer solution) and stir and ultrasonically disperse it evenly;
[0058] ② In a light-proof condition, 200 μL of 0.4 M N-(hexanoyloxy) succinimide was added dropwise to the fibrinogen solution under stirring, and the mixture was dispersed by a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted for 4 h at 37° C. to obtain a fibrinogen solution containing hydrophobic groups;
[0059] ③ The obtained fibrinogen solution containing hydrophobic groups was dialyzed at 4°C for 72 hours;
[0060] ④ Freeze the obtained fibrinogen solution containing hydrophobic groups and concentrate it to 100 mg / mL at a concentration temperature of 37° C.; then freeze-dry it to obtain a fibrinogen patch.
[0061] The hydrophobic modification reagent (N-(hexanoyloxy) succinimide) in the fibrinogen solution containing hydrophobic groups is not a simple mixture with the fibrinogen solution, but reacts with the primary amine of the lysine residue on the surface of the fibrinogen to form a stable amide bond and binds to the fibrinogen molecule.
[0062] The microstructure of the patch prepared in this embodiment is as follows Figure 1As shown, its surface has a porous structure. The hydrophobic group of fibrinogen in the patch is -CO-(CH2)4CH3, which reacts with the primary amine of the lysine residue on the surface of fibrinogen to form an amide bond (-NH-CO-). The van der Waals interaction between the hydrophobic chains is enhanced due to the close distance, inducing entanglement between protein molecules ( Figure 2 ), so that the patch has strong mechanical properties and adhesion properties. The stabilizers of the patch in this embodiment are Na2HPO4, KH2PO4, NaCl and KCl. In order to facilitate the comparison of the mechanical properties of different embodiments and comparative examples, the stabilizers in the following preparation processes remain the same. At the same time, the stabilizer in the present invention can also be one or more of sodium chloride, calcium chloride, potassium chloride, magnesium chloride, sodium citrate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, arginine hydrochloride, and glycine. The patch prepared in this embodiment contains 20 mg of fibrinogen containing hydrophobic groups per square centimeter.
[0063] The bonding energy of the patch in Example 1 is 160 J / m 2 , the shear strength is 8750 Pa. In addition, the time for the unmodified fibrinogen and the fibrinogen containing hydrophobic groups of the present invention to form fibrin gel catalyzed by thrombin is similar, indicating that the modified fibrinogen retains the ability to be recognized by thrombin ( Figure 3 The patch has a suitable pH value and low cytotoxicity ( Figure 4 ); 28 days after implantation into the wound area of rat liver, the wound healed well.
[0064] Example 2
[0065] ① Take a 100 mg / mL fibrinogen solution (PBS buffer solution) and stir and ultrasonically disperse it evenly;
[0066] ② Under light-proof conditions, 200 μL of 0.4 M 2,5-dioxopyrrolidin-1-yl dodecanoate was added dropwise to the fibrinogen solution under stirring conditions, and the mixture was dispersed under a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted at 37° C. for 5 h to obtain a fibrinogen solution containing hydrophobic groups;
[0067] ③ The obtained fibrinogen solution containing hydrophobic groups was dialyzed at 4°C for 72 hours;
[0068] ④ Freeze the obtained fibrinogen solution containing hydrophobic groups and concentrate it to 100 mg / mL at a concentration temperature of 37° C.; then freeze-dry it to obtain a fibrinogen patch.
[0069] The hydrophobic group of fibrinogen in the patch of this embodiment is -CO-(CH2) 10CH3 reacts with the primary amine of the lysine residue on the surface of fibrinogen to form an amide bond (-NH-CO-). The patch prepared in this example contains 20 mg of fibrinogen containing hydrophobic groups per square centimeter. The adhesion energy is 175 J / m 2 , and the shear strength is 10320 Pa. The patch has a suitable pH value and low cytotoxicity; after being implanted into the wound area of rat liver for 28 days, the wound healed well.
[0070] Example 3
[0071] ① Take a 100 mg / mL fibrinogen solution (PBS buffer solution) and stir and ultrasonically disperse it evenly;
[0072] ② Under light-proof conditions, 200 μL of 0.4 M methacrylate N-hydroxysuccinic acid imide was added dropwise to the fibrinogen solution under stirring conditions, and the mixture was dispersed under a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted at 37° C. for 3 h to obtain a fibrinogen solution containing hydrophobic groups;
[0073] ③ The obtained fibrinogen solution containing hydrophobic groups was dialyzed at 25°C for 24 hours;
[0074] ④ Freeze the obtained fibrinogen solution containing hydrophobic groups and concentrate it to 100 mg / mL at a concentration temperature of 4°C; then freeze-dry it to obtain a fibrinogen patch.
[0075] The hydrophobic group of fibrinogen in the patch of this embodiment is -CO-CH(CH3)=CH2, which contains a carbon-carbon double bond and reacts with the primary amine of the lysine residue on the surface of fibrinogen to form an amide bond (-NH-CO-). The patch prepared in this embodiment contains 20 mg of fibrinogen containing hydrophobic groups per square centimeter. The adhesion energy is 146 J / m 2 The shear strength is 7320 Pa. The patch has a suitable pH value and low cytotoxicity; after being implanted into the wound area of rat liver for 28 days, the wound healed well.
[0076] Example 4
[0077] ① Take a 100 mg / mL fibrinogen solution (PBS buffer solution) and stir and ultrasonically disperse it evenly;
[0078] ② Under light-proof conditions, 200 μL of 0.4 M 2,5-Dioxopyrrolidin-1-yl methyl glutarate was added dropwise to the fibrinogen solution under stirring conditions, and the mixture was dispersed under a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted at 37° C. for 3 h to obtain a fibrinogen solution containing hydrophobic groups;
[0079] ③ The obtained fibrinogen solution containing hydrophobic groups was dialyzed at 25°C for 24 hours;
[0080] ④ Freeze the obtained fibrinogen solution containing hydrophobic groups and concentrate it to 100 mg / mL at a concentration temperature of 37° C.; then freeze-dry it to obtain a fibrinogen patch.
[0081] The hydrophobic group of fibrinogen in the patch of this embodiment is -CO-(CH2)3-COOCH3, which contains an ester group and reacts with the primary amine of the lysine residue on the surface of fibrinogen to form an amide bond (-NH-CO-). The patch prepared in this embodiment contains 20 mg of fibrinogen containing hydrophobic groups per square centimeter. The adhesion energy is 156 J / m 2 , and the shear strength is 8568 Pa. The patch has a suitable pH value and low cytotoxicity; after being implanted into the wound area of rat liver for 28 days, the wound healed well.
[0082] Example 5
[0083] ① Take a 100 mg / mL fibrinogen solution (PBS buffer solution) and stir and ultrasonically disperse it evenly;
[0084] ② Under light-shielding conditions, 200 μL of 0.4 M 1-(2,5-Dioxopyrrolidin-1-yl)8-methyl octanedioate was added dropwise to the fibrinogen solution under stirring, and the mixture was dispersed by a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted for 3 h at 37° C. to obtain a fibrinogen solution containing hydrophobic groups;
[0085] ③ The obtained fibrinogen solution containing hydrophobic groups was dialyzed at 25°C for 24 hours;
[0086] ④ Freeze the obtained fibrinogen solution containing hydrophobic groups and concentrate it to 100 mg / mL at a concentration temperature of 37° C.; then freeze-dry it to obtain a fibrinogen patch.
[0087] The hydrophobic group of fibrinogen in the patch of this embodiment is -CO-(CH2)5-COOCH3, which contains an ester group and reacts with the primary amine of the lysine residue on the surface of fibrinogen to form an amide bond (-NH-CO-). The patch prepared in this embodiment contains 20 mg of fibrinogen containing hydrophobic groups per square centimeter. The adhesion energy is 159 J / m 2 The shear strength is 8850 Pa. The patch has a suitable pH value and low cytotoxicity; after being implanted into the wound area of rat liver for 28 days, the wound healed well.
[0088] Comparative Example 1
[0089] ① Take a 100 mg / mL fibrinogen solution (PBS buffer solution) and stir and ultrasonically disperse it evenly;
[0090] ② In a light-proof condition, 200 μL of PBS solution was added dropwise to the fibrinogen solution under stirring, and the mixture was dispersed by a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted for 4 h at 37° C. to obtain an unmodified fibrinogen solution;
[0091] ③ The obtained unmodified fibrinogen solution was dialyzed at 4°C for 72 hours.
[0092] ④ Freeze the obtained unmodified fibrinogen solution and concentrate it to 100 mg / mL at a concentration temperature of 37°C; then freeze-dry it to obtain an unmodified fibrinogen patch (during the freeze-drying process, the intermolecular interactions of the unmodified fibrinogen are relatively weak, and the formed patch is not formed).
[0093] The difference between Comparative Example 1 and Example 1 is that there is no hydrophobic group modification. The patch prepared in this example contains 20 mg of fibrinogen per square centimeter.
[0094] Bonding energy is 10J / m 2 , the shear strength is 1233 Pa. The mechanical properties and adhesion properties of the unmodified fibrinogen patch are much lower than those of the patch described in the present invention ( Figure 5 and Figure 6 ). This shows that hydrophobic group modification is a key factor in improving the performance of the fibrinogen patch of the present invention.
[0095] Comparative Example 2
[0096] (1) Fibrinogen solution containing hydrophobic groups:
[0097] ① Take a 100 mg / mL fibrinogen solution (PBS buffer solution) and stir and ultrasonically disperse it evenly;
[0098] ② In a light-proof condition, 200 μL of 0.4 M N-(hexanoyloxy) succinimide was added dropwise to the fibrinogen solution under stirring, and the mixture was dispersed by a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted for 4 h at 37° C. to obtain a fibrinogen solution containing hydrophobic groups;
[0099] ③ The obtained fibrinogen solution containing hydrophobic groups was dialyzed at 4°C for 72 hours.
[0100] (2) Unmodified fibrinogen solution:
[0101] ① Take a 100 mg / mL fibrinogen solution (PBS buffer solution) and stir and ultrasonically disperse it evenly;
[0102] ② Under light-proof conditions, the fibrinogen solution was added dropwise to 200 μL of PBS solution under stirring conditions, and dispersed under a triple mixing process of vortexing for 5 minutes and ultrasonication for 5 minutes, and reacted at 37° C. for 4 hours to obtain an unmodified fibrinogen solution;
[0103] ③ The obtained unmodified fibrinogen solution was dialyzed at 4°C for 72 hours.
[0104] The adhesion energy of the fibrinogen solution containing hydrophobic groups is 7.5 J / m 2 , the shear strength is 800Pa. The mechanical properties of the patch of Example 1 of the present invention are much better than those of the fibrinogen solution containing hydrophobic groups obtained in this example, indicating that the present invention needs to form a patch to achieve excellent mechanical effects. On the one hand, the patch of the present invention can increase the adhesion performance with the tissue by absorbing water; on the other hand, in the process of removing water to form a patch, the van der Waals interaction between the hydrophobic chains is enhanced due to the close distance, which makes the fibrinogen patch have strong mechanical properties. The patch form described in the present invention plays an important role in its overall performance.
[0105] The adhesion energy of unmodified fibrinogen solution is 6.5 J / m 2 , and the shear strength is 750 Pa. It can be seen that there is no obvious difference in solution viscosity and mechanical properties between the fibrinogen solution containing hydrophobic groups and the unmodified fibrinogen solution.
[0106] Comparative Example 3
[0107] (1) Gelatin patches modified with hydrophobic groups and unmodified gelatin patches
[0108] Gelatin patch modified with hydrophobic groups:
[0109] ① Take a gelatin solution (PBS buffer solution) with a mass fraction of 100 mg / mL, stir and disperse it evenly by ultrasonication;
[0110] ② In a light-proof condition, 200 μL of 0.4 M N-(hexanoyloxy) succinimide was added dropwise to the gelatin solution under stirring, and the mixture was dispersed by a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted for 4 h at 37° C. to obtain a gelatin solution containing a hydrophobic group;
[0111] ③ The obtained gelatin solution containing hydrophobic groups was dialyzed at 37°C for 72 hours;
[0112] ④ Freeze the obtained gelatin solution containing hydrophobic groups and concentrate it to 100 mg / mL at a concentration temperature of 37°C; then freeze-dry it to obtain a hydrophobic group-modified gelatin patch. The patch prepared in this example contains 20 mg of modified gelatin per square centimeter.
[0113] Unmodified Gelatin Patches:
[0114] ① Take a gelatin solution (PBS buffer solution) with a mass fraction of 100 mg / mL, stir and disperse it evenly by ultrasonication;
[0115] ② In a light-proof condition, 200 μL of PBS solution was added dropwise to the gelatin solution under stirring, and the mixture was dispersed by a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted for 4 h at 37° C. to obtain an unmodified gelatin solution;
[0116] ③ The unmodified gelatin solution was dialyzed at 37°C for 72 hours;
[0117] ④ Freeze the obtained unmodified gelatin solution and concentrate it to 100 mg / mL at a concentration temperature of 37°C; then freeze-dry it to obtain an unmodified gelatin patch. The patch prepared in this example contains 20 mg of gelatin per square centimeter.
[0118] (2) Albumin patches modified with hydrophobic groups and unmodified albumin patches
[0119] Albumin patch modified with hydrophobic groups:
[0120] ① Take a 100 mg / mL bovine serum albumin solution (PBS buffer solution), stir and ultrasonically disperse it evenly;
[0121] ② Under light-proof conditions, the bovine serum albumin solution was dropwise added with 200 μL of 0.4 M N-(hexanoyloxy) succinimide under stirring conditions, and dispersed under a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted for 4 h at 37° C. to obtain an albumin solution containing hydrophobic groups;
[0122] ③ The obtained albumin solution containing hydrophobic groups was dialyzed at 4°C for 72 hours;
[0123] ④ Freeze the obtained albumin solution containing hydrophobic groups and concentrate it to 100 mg / mL at a concentration temperature of 37°C; then freeze-dry it to obtain an albumin patch modified with hydrophobic groups. The patch prepared in this example contains 20 mg of modified albumin per square centimeter.
[0124] Unmodified Albumin Patch:
[0125] ① Take a 100 mg / mL bovine serum albumin solution (PBS buffer solution), stir and ultrasonically disperse it evenly;
[0126] ② In a light-proof condition, 200 μL of PBS solution was added dropwise to the bovine serum albumin solution under stirring, and the mixture was dispersed by a triple mixing process of vortexing for 5 min and ultrasonication for 5 min, and reacted for 4 h at 37° C. to obtain an unmodified albumin solution;
[0127] ③ The unmodified albumin solution was dialyzed at 4°C for 72 hours;
[0128] ④ Freeze the obtained unmodified albumin solution and concentrate it to 100 mg / mL at a concentration temperature of 37°C; then freeze-dry it to obtain an unmodified albumin patch. The patch prepared in this example contains 20 mg of albumin per square centimeter.
[0129] In the comparative example, the gelatin patch modified with hydrophobic groups and the unmodified gelatin patch, and the albumin patch modified with hydrophobic groups and the unmodified albumin patch, did not show significant changes in patch mechanical properties and tissue adhesion properties before and after hydrophobic group modification. Moreover, regardless of the gelatin and albumin before or after modification, after freeze-drying, they did not actually form a patch structure, but were in powder form, and were not the patch described in the present invention.
[0130] This shows that when hydrophobic groups are modified on the fibrinogen molecule, it can form a patch instead of a powder after freeze-drying, and the freeze-dried fibrinogen has strong mechanical properties. Under the same conditions, gelatin and albumin do not produce the corresponding phenomenon. We speculate that the morphology and mechanical property enhancement of the fibrinogen patch are related to its own composition characteristics. Fibrinogen is composed of two symmetrical halves, each of which contains three polypeptide chains Aα, Bβ and γ, and is a linear protein molecule. Due to its special composition and structure, after modification with hydrophobic groups, the mechanical properties are unexpectedly improved.
[0131] Comparative Example 4
[0132] Three surgical adhesive products purchased from commercial channels (absorbable): Surgicel Fibrillar from Johnson & Johnson, Fibrin Glue from Shanghai Laishi, and Gelatin Sponge from Xiangen;
[0133] There are four commercially available emergency hemostatic products (non-absorbable, for extracorporeal use): QuikClot Combat Gauze (kaolin impregnated into gauze), Celox Gauze hemostat (chitosan laminated into gauze), ChitoSAM 100 (nonwoven fabric spun from chitosan), and HemCon ChitoGauze (chitosan loaded into gauze).
[0134] The three surgical adhesive products selected in this comparative example are widely used in the prior art and have better performance than similar products; the four emergency hemostatic products selected are the main representatives used for massive bleeding in daily accidents, wars, and natural disasters. Whether it is the existing surgical adhesive products or the emergency hemostatic materials, their tissue adhesion and hemostatic properties need to be further improved.
[0135] By comparing the three surgical adhesive products (absorbable, for in vitro use; Fibrin Glue, Surgicel Fibrillar, Gelatin Sponge) of Example 1, Comparative Example 1 and Comparative Example 4, it can be found that the fibrinogen patch of the present invention is significantly higher in shear strength and adhesion energy than the three surgical adhesive products ( Figure 5 and Figure 6 ). At the same time, the patch of the present invention is also significantly superior to commercial fibrin glue in terms of mechanical properties, and is expected to become a new type of tissue sealant.
[0136] In the New Zealand rabbit liver hemostasis experiment (surgical trauma model), the hemostatic function of sealants of the same / similar form (patch / sponge) was compared. The fibrinogen patch of the present invention (Example 1) was compared with the surgical adhesive products of Comparative Example 1 (unmodified fibrinogen patch) and Comparative Example 4 (Surgicel Fibrillar, Gelatin Sponge). Due to the excellent mechanical strength and adhesion properties of the fibrinogen patch of the present invention, it showed a shorter hemostasis time and less blood loss, showing excellent hemostatic performance ( Figure 7 ).
[0137] The four emergency hemostatic products (non-absorbable, for in vitro use; Combat Gauze, HemCon, Celox, ChitoSAM) of Example 1 and Comparative Example 4 are compared. These four emergency hemostatic products are all recommended for hemostasis in cases of massive bleeding. The principle mainly relies on the procoagulant properties of the material itself, but the hemostatic efficiency needs to be further improved. The fibrinogen patch of the present invention has excellent mechanical strength and adhesion properties, and can have a good adhesion effect at the bleeding injury site. Therefore, the hemostatic performance is significantly better than the emergency hemostatic products Combat Gauze, HemCon, Celox and ChitoSAM ( Figure 8 ).
[0138] In summary, the fibrinogen patch of the present invention is significantly superior to the surgical adhesive products and emergency hemostasis products in the prior art in terms of both adhesion and hemostasis performance. At the same time, the patch unexpectedly invented by the present invention has good biocompatibility and can be absorbed by the human body. The patch of the present invention is excellent in both performance and safety, and has great potential in clinical applications.
Claims
1. A fibrinogen-based patch, characterized in that: The patch comprises fibrinogen and a stabilizer, wherein some lysine residues of the fibrinogen contain hydrophobic groups; and the stabilizer is used to maintain the activity of the fibrinogen; The patch contains no less than 2 mg of fibrinogen containing hydrophobic groups per square centimeter; The lysine residues containing hydrophobic groups on the fibrinogen account for 2% to 70% of the total number of lysine residues, by number; The hydrophobic group is a hydrocarbon group containing one or more groups of carbonyl, carbon-carbon double bond, ester group, amide bond, and phenyl group; The stabilizer is one or more of sodium chloride, calcium chloride, potassium chloride, magnesium chloride, sodium citrate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, arginine hydrochloride, and glycine.
2. The fibrinogen-based patch according to claim 1, characterized in that The hydrophobic group forms an amide bond (-NH-CO-) with the primary amine of the lysine residue of fibrinogen.
3. The fibrinogen-based patch according to claim 1, characterized in that The patch contains a pharmaceutically active ingredient.
4. The method for preparing a fibrinogen patch according to claim 1, characterized in that: The specific steps include: ① subjecting the mixed solution of fibrinogen and stabilizer to ultrasonic treatment, and obtaining a fibrinogen solution with a mass fraction of 5 to 200 mg / mL; ② adding a hydrophobic modification reagent dropwise to the fibrinogen solution under stirring, reacting at 37° C. for 0.5 to 5 hours to obtain a fibrinogen solution containing a hydrophobic group; ③ The obtained fibrinogen solution containing hydrophobic groups is dialyzed at 4-37°C for 5-72 hours; ④ Concentrating the obtained fibrinogen solution containing hydrophobic groups to 50-200 mg / mL at a concentration temperature of 4-37° C.; and freeze-drying at a freeze-drying temperature of -85--35° C. to obtain the fibrinogen-based patch; The hydrophobic modification reagent contains a hydrophobic group, which is used to modify the lysine residue of fibrinogen; the hydrophobic modification reagent also contains a succinimide group, which is used to react with the primary amine of the lysine residue to form a stable amide bond.
Citation Information
Patent Citations
Method and substance for keeping fibrinogen activity in thermal treatment
CN101544683A
Cited By
Hydrogel adhesive based on gelatin and clay material and preparation method thereof
CN120267879A